Detection of damage location using mode shape deviation: Numerical study - Fayyadh, M.M.; Abdul Razak, H. (2011)
This study presents the use of mode shapes for the identification of damage location. The residual values from curve fitting procedure on mode shape vectors with Chebyshev standard rational series were used to detect the damage along the beam length. The results showed that all the mode shapes for the damaged cases deviated from that of the undamaged case, where the deviation was towards the damage location. The results also showed that the residual from curve fitting procedure for all mode shapes have higher values around the damaged element along the beam length which made it a good indicator for damage location.